Investigation of genetic diversity among autochthonous grape cultivars grown in Türkiye using molecular primers - Ahmet Sümbül; Ercan Yildiz; Ali Sabir; Muhammad Azhar Nadeem (Genetic Resources and Crop Evolution, 2024)
Grape is a type of fruit widely grown globally and in Türkiye thanks to its importance in human nutrition and diversity of usage areas. Türkiye has a long history of grape cultivation, and the genetic diversity of local grapes grown in some regions has still not been revealed. This study showed the genetic diversity between 60 local grape genotypes selected from north Central Anatolia and nine reference grape cultivars;10 inter simple sequence repeats (ISSR) and 7 inter-primer binding site (IPBS) retrotransposon primers were used. The mean values of genetic diversity indices in ISSR and IPBS retrotransposon primers were calculated as expected allelic frequency (p) 0.476/0.195, observed allelic frequency (q) 0.524/0.805, number of effective alleles (Ne) 1.326/1.378, Shannon’s information index (I) 0.308/0.367, expected heterozygosity (He) 0.199/0.232 and unbiased expected heterozygosity (uHe) 0.201/0.234, respectively. Unweighted pair group method with arithmetic mean (UPGMA) and model-based STRUCTURE analysis divided the studied germplasm into two groups. However, local genotypes were not grouped per the regions where they grew. As a result of the analysis of molecular variance (AMOVA) analysis, the inter-population variation was determined to be 11%, and the intra-population variation was determined to be 89%. The mean genetic differentiation value (Fst) between populations was 0.303. The results showed that ISSR and IPBS retrotransposon primers effectively explained the genetic diversity.